Application of carbazole derivatives as a multifunctional material for organic light-emitting devices - Ivaniuk, Khrystyna; Kutsiy, Stepan; Shchetinin, Mykhailo; Bulavinets, Tetiana; Yaremchuk, Iryna (Technology audit and production reserves, 2024)
The object of research is newly synthesized carbazole-derived compounds and organic light-emitting structures based on them. The problem lies in the complex solution of scientific and technical problems of improving the characteristics and stability of organic light-emitting diodes (OLEDs), namely improving the brightness and energy-efficient parameters. Organic light-emitting structures of blue, blue, and green radiation with color coordinates were formed by the thermovacuum sputtering method and the solution deposition method. The turn-on voltage of the white OLED is 6 V, the maximum brightness of the light-emitting structures was 10,000 cd/m2. The devices demonstrated a sufficiently high external quantum efficiency of 5 % to 7 %. This paper reports the multifunctional application of a simple donor-acceptor organic compound, as active and host material in the emission layer of organic light emitting devices. Em1 has been used as active components in OLEDs, where Em1 is the guest emitter (Device A), the acceptor part of the excited emitter (Device B) and the host matrix of the CdSeS/ZnS alloy quantum dot. At least four different OLEDs have been designed and characterized where Em1 plays the role of the guest emitter (Device C). The external quantum efficiencies of devices A–C are characterized by values common to pure fluorescent OLEDs (up to 5 % of the theoretical limit), but these devices sustain low-efficiency roll-off of electroluminescence over a wide range of current densities. Organic light-emitting diodes based on carbazole-derived compounds, due to their color characteristics, are promising candidates for use in the latest lighting systems. A separate advantage of the data light-emitting structures is a multifunctional application of one compound for different types of light-emitting structures. In addition, organic LEDs on based on carbazole-derived compounds have low energy consumption and are environmentally friendly due to the absence of toxic substances in their architecture, which creates prerequisites for saving energy resources and reducing the industrial burden on the environment.